1998
DOI: 10.1002/(sici)1097-4636(199811)42:2<272::aid-jbm12>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The effect on immunocytes of anodic oxide titanium after hydrothermal treatment

Abstract: All dental root implants come in contact with the oral epithelium, and many complex factors are found to arise in this region. In order to perform a successful dental root implantation, it is necessary to clarify the interaction of the dental root implant material with the host defense mechanisms involved in the specific and nonspecific immune responses to many antigens in oral bacteria and their components. Recently, focusing on developing the dental root implant, the Nikon Corporation improved the surface ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…The oxide layer enriched in this way is characterized by increased biotolerance. The biotolerance of titanium anodized in a solution containing calcium and phosphorus can be additionally improved by means of a hydrothermal treatment [25][26][27]. Moreover, the application of plasma electrolytic oxidation in solutions containing calcium and phosphorus leads to an increase of corrosion resistance of titanium in physiological saline solutions [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The oxide layer enriched in this way is characterized by increased biotolerance. The biotolerance of titanium anodized in a solution containing calcium and phosphorus can be additionally improved by means of a hydrothermal treatment [25][26][27]. Moreover, the application of plasma electrolytic oxidation in solutions containing calcium and phosphorus leads to an increase of corrosion resistance of titanium in physiological saline solutions [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that a HA/cpTi surface promotes early production and mineralization of bone matrix,14, 15 and early bone formation. A HA/cpTi surface is compatible with bone tissue,16 and has no adverse effect on immune cells 17. Furthermore, the thin HA layer formed on HA/cpTi increases in stability during the process of bone matrix mineralization 18.…”
Section: Introductionmentioning
confidence: 99%
“… No genotype testing: Perala et al (1992), Kao et al (1995), Mengel et al (1996), Lamster et al (1996), Panagakos et al (1996), Salcetti et al (1997), Cuenin et al (1997), Curtis et al (1997), Aboyoussef et al (1998), Schierano et al (2003), Pietruski et al (2001), Hultin et al (2002), Murata et al (2002), Schultze‐Mosgau et al (2006), Konttinen et al (2006), Liskmann et al (2006), Machtei et al (2006), Lachmann et al (2007b). In vitro studies: Koka & Reinhardt (1997), Wakabayashi et al (1997), Takebe et al (1998), Reyes‐Botella et al (2002), Ataoglu et al (2002), Spyrou et al (2002), Schierano et al (2003). Experimental studies: Katsuki et al (1998), Nor et al (2001), Schierano et al (2005). No data on oral implants: Becker & Rosenbaum (2000), Rhoton‐Vlasak et al (2005). Review article: Greenstein & Hart (2002a, 2002b), Nares (2003), Hwang & Wang (2007). Cross‐sectional design: Campos et al (2005a), Lachmann et al (2007a). …”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies: Koka & Reinhardt (1997), Wakabayashi et al (1997), Takebe et al (1998), Reyes‐Botella et al (2002), Ataoglu et al (2002), Spyrou et al (2002), Schierano et al (2003).…”
Section: Resultsmentioning
confidence: 99%